Characterizing carbapenemase-producing Escherichia coli isolates from Spain: high genetic heterogeneity and wide geographical spread - Dahdouh, Elias; Gómez-Marcos, Laro; Cañada-García, Javier E.; de Arellano, Eva Ramírez; Sánchez-García, Aida; Sánchez-Romero, Isabel; López-Urrutia, Luis; de la Iglesia, Pedro; Gonzalez-Praetorius, Alejandro; Sotelo, Jared; Valle-Millares, Daniel; Alonso-González, Isabela; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Carbapenemase-Producing Escherichia coli (CP-Eco) isolates, though less prevalent than other CP-Enterobacterales, have the capacity to rapidly disseminate antibiotic resistance genes (ARGs) and cause serious difficult-to-treat infections. The aim of this study is phenotypically and genotypically characterizing CP-Eco isolates collected from Spain to better understand their resistance mechanisms and population structure.Ninety representative isolates received from 2015 to 2020 from 25 provinces and 59 hospitals Spanish hospitals were included. Antibiotic susceptibility was determined according to EUCAST guidelines and whole-genome sequencing was performed. Antibiotic resistance and virulenceassociated genes, phylogeny and population structure, and carbapenemase genes-carrying plasmids were analyzed.The 90 CP-Eco isolates were highly polyclonal, where the most prevalent was ST131, detected in 14 (15.6%) of the isolates. The carbapenemase genes detected were blaOXA-48 (45.6%), blaVIM-1 (23.3%), blaNDM-1 (7.8%), blaKPC-3 (6.7%), and blaNDM-5 (6.7%). Forty (44.4%) were resistant to 6 or more antibiotic groups and the most active antibiotics were colistin (98.9%), plazomicin (92.2%) and cefiderocol (92.2%). Four of the seven cefiderocol-resistant isolates belonged to ST167 and six harboured blaNDM. Five of the plazomicin-resistant isolates harboured rmt. IncL plasmids were the most frequent (45.7%) and eight of these harboured blaVIM-1. blaOXA-48 was found in IncF plasmids in eight isolates. Metallo-β-lactamases were more frequent in isolates with resistance to six or more antibiotic groups, with their genes often present on the same plasmid/integron. ST131 isolates were associated with sat and pap virulence genes.This study highlights the genetic versatility of CP-Eco and its potential to disseminate ARGs and cause community and nosocomial infections.